Low achievers and the quest for institutional standard in mathematics education: A phenomenology of subject matter experts’ opinions from Nigerian higher education - Joshua Abah ABAH (Universitas Islam Negeri Maulana Malik Ibrahim, 2018)
This study adopts a phenomenological paradigm to present mathematics experts’ opinions on the existence of low achievers in Nigeria’s higher education system. Six career mathematicians volunteered from among the participants at a conference of one of Nigeria’s elite academic group to give their in-depth opinion on the role of educational institutions in handling low achievers, their impact on Nigeria’s quest for quality education, and personal approaches for managing low achievers in the mathematics classroom. The explication of the responses of the mathematics experts indicates concerns about the admission system of higher educational institutions and some pertinent pedagogical inadequacies of pure mathematicians. The study also revealed that the continual existence of low achievers in the discipline encourages high rate of dropping-out, poor quality of mathematics educators, and examination malpractice. Participants suggest counseling intervention, retraining of mathematics lecturers in teaching methodologies, and special mindset-boosting programmes as ways of handling low achievers in mathematics education. The phenomenology also unveiled certain unintended outcomes that may form the basis for future research into the peculiar attitudinal characteristics of academic mathematicians.